Experiences with an Extraperitoneal Transvesicoscopic Repair of a Vesicovaginal Fistula - Kim, Hongwook; Hong, ChangHee; Kim, JangHwan (Urology Journal, 2023)
Purpose: A vesicovaginal fistula (VVF) is a debilitating condition for women in terms of both its personal and social impacts. A reported transperitoneal laparoscopic approach to treatment has some limitations such as risk of intra-peritoneal organ injury and unnecessary bladder dissection. We here report on our experiences with an extraperitoneal transvesicoscopic approach to a VVF repair, which overcomes these drawbacks. Materials and Methods: Seven VVF patients were treated using the transvesicoscopic approach. Under general anesthesia, patients were placed in the dorsal lithotomy position. The VVF orifice was obstructed via the vaginal canal using a Foley catheter. The bladder was then filled with normal saline under cystoscopic inspection, and a 5 mm trocar was inserted into it at the suprapubic area. The bladder wall was next fixed to the anterior abdominal wall. Thereafter, two 3 mm ports were punctured at the interspinous skin crease allowing the fistula margin to be cut and sutured in layers. Results: Six of the study subjects in whom we attempted a transvesicoscopic repair of VVF had undergone a hysterectomy due to myoma and one had an intraabdominal abscess removal with Behcet's disease. One myoma patient who had a preexisting vesicoperitoneal fistula was converted to an open transabdominal VVF repair. The mean age of the 6 remaining patients was 46.0 ± 7.2 years (range, 35-57). The mean operation time was 273 ± 40.6 minutes (range, 223-323). There was no instances of significant pain or other immediate complications. Five patients showed no recurrence of the fistula during the follow-up period (8.7 ± 5.1 months). Conclusion: A transvesicoscopic approach is an effective modality for the repair of a VVF that is more minimally invasive and has a lower morbidity than a transabdominal procedure.